Existence of bounded solutions for a non-periodic sublinear equation - Peng, Yaqun (Journal of Differential Equations, 2025)
We prove that u¨+|u|α−1u=p(t),0<α<1 has infinitely many bounded solutions for bounded and measurable forcing p by the implicit function theorem and the non-periodic twist theory established by Kunze and Ortega.